Resonant Power Converters for Renewable Energy Applications: A Comprehensive Review - Bughneda, Ali; Salem, Mohamed; Alhuyi Nazari, Mohammad; Ishak, Dahaman; Kamarol, Mohamad; Alatai, Salah (Frontiers in Energy Research, 2022)
Studies on resonant power converters have received quite an attention especially when there has been a rapid growth and rise of potential in modern power and renewable energy applications such as photovoltaic, electric vehicles, wind and fuel cells. Consequently, a significant number of studies focusing on resonant converter topologies for renewable energy applications is available. Generally, these studies have addressed a number of aspects such as the development of their features of soft switching, high power density, smooth waveforms and high efficiency. With this in mind, the present paper aims to review the development of the resonant converters, challenges in their development, and comparison between common topologies as highlighted in literature. In addition, the use of resonant converters in various applications of renewable energy is highlighted. From the review, there are still a number of issues and challenges in research that need to be considered for future improvement of the resonant converter performance in renewable energy applications. The improvement may require modifications on the circuit design or control strategies.